The Effect of Cloud-Based Accounting System Implementation on Real-Time Financial Reporting Quality: Evidence from Indonesian Firms - Dewi Masitah; Siti Aisyah Hidayati; Ayudia Sokarina (The Indonesian Accounting Review, 2026)
The increasing use of cloud-based accounting systems has transformed how organizations record their transactions and produce their financial reports. While previous studies primarily emphasize the adoption of cloud accounting technologies, limited empirical attention has been given to how the depth of system implementation influences financial reporting quality. This study examines the effect of cloud-based accounting system implementation on real-time financial reporting quality in Indonesian firms. Using a quantitative research design, data were collected from 120 respondents representing 20 Indonesian firms operating across several sectors, including retail, hospitality, property development and services. The data were analyzed using structural equation modeling partial least squares (SEM-PLS). The findings indicate that the deeper implementation of cloud-based accounting systems improves the quality of real-time financial reporting, particularly in terms of the timeliness, accuracy, reliability, relevance, and clarity of financial information. By conceptualizing implementation as a multidimensional construct, including system use, feature utilization, system integration, and user competence, this study shifts the analytical focus from technology adoption to implementation effectiveness. The results highlight that the benefits of cloud-based accounting systems depend not only on technological adoption but also on how effectively the systems are embedded in organizational accounting practices.